A commentary on Hesiod : Works and days, vv. l-382 - Verdenius, W. J. (Mnemosyne, Supplements, 1985)
This is a word-for-word commentary on the first part (vv. 1-382) of Hesiod's Works and Days . Special attention has been paid to peculiarities of grammar and idiom, but also to figures of style and the poet's train of thought. All interpretations - many of them which are new - are documented as fully, but at the same time as concisely, as possible. This documentation, which will prove useful for the interpretation of many other texts, has been made more easily accesible by detailed indexes. Discussion of other views plays a considerable part in the commentary and will help the reader avoid a great number of minor and major misunderstandings. The commentary has been confined to the first part of the poem because this seemed to be more in need of a thorough explanation than the rest. It is also the most interesting part in so far as it forms a kind of manual of social morality. The basis concepts of this doctrine are carefully defined in the commentary, and their historical implications are briefly indicated.